Analysis on The Roles of Stakeholders in The Management of Integrated Breeding Beef Cattle Farm Program at PT KPC East Kutai - J Ariansyah; A Ismail; L Abdullah (Media Peternakan, 2013)
An analysis of the roles of stakeholders was conducted as a continuity program of Peternakan Sapi Terpadu (PESAT; integrated beef cattle farm) following the coal mining deactivation by PT Kaltim Prima Coal (KPC) of East Kutai, East Kalimantan. The purpose of this study was to formulate stakeholders relation in the future program. The stakeholders involved in this program were PT KPC, local breeders, Sekolah Tinggi Ilmu Pertanian (STIPER; Agriculture Academy) of East Kutai, and the local government of East Kutai. The stakeholders analysis was based on the variables of the importance and influence from every analyzed stakeholder. The analysis model used here was the model introduced by Reed et al. (2009). According to the result of the stakeholders analysis, PT KPC was in the key-player quadrant, which score is 25 in both of the interest and the influencial level,  while the three others, such as, local breeders, STIPER of East Kutai, and the East Kutai Government were in the subject quadrant. Their score were 24 and 7 for Local breeders, 21 and 9 for STIPER of East Kutai, and 16 and 13 for The East Kutai Government.  It means, they had high interest but low influence to the program. The conclusion of this analysis shows that PT KPC is still dominating in the PESAT program management, whereas the three other stakeholders are acting merely as program users that have low involvement in the program management.